(untitled) (Regional aspects of productive forces development of Ukraine, 2024)
ABSTRACT Introduction. The revolution in human resource management in the digital era is undoubtedly driven by key factors that represent a significant change in the approach to human resource management in the modern world. Continuous technological development and digitalization of business are increasingly creating the need for more efficient, flexible and innovative HR practices. The current challenges of globalization, the transition from an industrial economy to a networked digital economy, new speeds, mobility and transparency of business require a rethinking of the business paradigm. The ongoing digital revolution requires the transformation of traditional companies into technology companies. Business rules are changing to ensure success in the fast-paced digital age. However, there is still a lack of in-depth research on the integration of digital technologies into HR processes and the definition of the main components of digital HR. Therefore, the questions selected for analysis are extremely important. Goal. To achieve this goal, a set of general scientific methods of cognition was applied, which ensured the consistency and logical consistency of the conclusions drawn. Methods. To achieve this goal, a set of general scientific methods of cognition, including instrumental, institutional, graphic, were used. Results. It has been established that digital technologies in HR help automate routine tasks, reduce errors, and increase the efficiency and convenience of processes for employees and HR professionals. They can collect more data, make processes transparent, fast, and objective, which is the basis for making more informed and strategic decisions. As a result, the organization maintains its competitive of HR management and employee engagement. Conclusions. The findings allow us to optimize traditional processes and create new opportunities for integrating strategic HR management with the company’s overall business strategy, in particular, defining digital technologies in the context of the organization’s culture, which may be an area for further research. Key words: digitalization, digital technologies, HR revolution, HR processes, Digital HR components, HR functions.